Sun drying of residual annatto seed powder - Dyego da Costa Santos; Alexandre José de Melo Queiroz; Rossana Maria Feitosa de Figueirêdo; Emanuel Neto Alves de Oliveira (Acta Scientiarum: Technology, 2015)
Residual annatto seeds are waste from bixin extraction in the food, pharmaceutical and cosmetic industries. Most of this by-product is currently discarded; however, the use of these seeds in human foods through the elaboration of powder added to other commercial powders is seen as a viable option. This study aimed at drying of residual annatto powder, with and without the oil layer derived from the industrial extraction of bixin, fitting different mathematical models to experimental data and calculating the effective moisture diffusivity of the samples. Powder containing oil exhibited the shortest drying time, highest drying rate (≈ 5.0 kg kg-1 min-1) and highest effective diffusivity (6.49 × 10-12 m2 s-1). All mathematical models assessed were a suitable representation of the drying kinetics of powders with and without oil, with R2 above 0.99 and root mean square error values lower than 1.0.